A Real-Business-Cycle model with pollution and environmental taxation: the case of Bulgaria - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
We introduce an environmental dimension into a real-business-cycle model augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of utility-enhancing environmental quality, and the mechanics of environmental ("carbon") tax on polluting production, as well as the effect of government spending on pollution abatement over the cycle. In particular, a positive shock to pollution emission in the model works like a positive technological shock, but its effect is quantitatively very small. Allowing for pollution as a by-product of production improves the model performance against data, and in addition this extended setup dominates the standard RBC model framework, e.g., Vasilev (2009).
Keywords: E32; C68; Q58; 330; Business cycles; pollution; environmental quality; environmental tax; abatement spending